If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = -31 + m Solving -6 = -31 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. -6 + -1m = -31 + m + -1m Combine like terms: m + -1m = 0 -6 + -1m = -31 + 0 -6 + -1m = -31 Add '6' to each side of the equation. -6 + 6 + -1m = -31 + 6 Combine like terms: -6 + 6 = 0 0 + -1m = -31 + 6 -1m = -31 + 6 Combine like terms: -31 + 6 = -25 -1m = -25 Divide each side by '-1'. m = 25 Simplifying m = 25
| 660x(1-15x)=0 | | 0.7w+16+4w=27.38 | | 4n^2-6n+6=0 | | -6+10n=-76 | | -4x+6(2x-12)=24 | | 119=5x+11 | | 4x+-5=10-2 | | 45x=550 | | 6x+9-8(x+1)=3x+4 | | -14=23x | | 13+13x=-481 | | 7x/8-3x/8=1 | | 3n+4-n=12+n | | 6x-4(-4x+3)=186 | | 6+1/4(32x-8x)=27 | | -7x+5(6x-4)=-158 | | 60x=550 | | 6x-1=63 | | -x-6y=30 | | -2x+3(-7x+17)=-133 | | 200m-125m+43,425=45,000-150m | | 6x-7(-3x+4)=188 | | (2x+20)+(6x+24)=180 | | 9y-2(y-6)=3(2y+4) | | -12a+10=-62 | | -2x+7(3x+18)=-102 | | 30x-20=15x-12 | | 2(3x-7)+x=4-6x | | 80+9t=7t | | 6y-2(5+3y)=15 | | -6x-2(5x-5)=-118 | | 3m-15=-5 |